Iron Oxide Powder as Responsible for the Generation of Industrial Polypropylene Waste and as a Co-Catalyst for the Pyrolysis of Non-Additive Resins (2022)
For the synthesis of polymeric resins, it is of great importance to review the raw materials and the equipment to be used to avoid the presence of compounds that may affect the effectiveness of the polymerization and the characteristics of the plastic to be obtained. Iron oxide is a compound that can be present in reactors after maintenance due to the techniques used and the cleaning of this equipment, and it can affect the characteristics of the resins, reducing their quality. In this study, the presence of FeO in different concentrations was evaluated to determine its effects on the properties and pyrolysis of polypropylene resins by using X-ray refraction to determine the elements of the samples, evaluating thermal degradation by TGA, the variation in molecular weight by measuring the MFI, and the compounds obtained from pyrolysis by chromatography. The results showed that the thermal degradation decreased as the FeO concentration increased, while for the MFI, the relationship was directly proportional. The evaluation of the compounds obtained from pyrolysis showed an increase in the production of alcohols, alkynes, ketones, and acids, and a decrease in alkanes and alkenes, showing that FeO affects the properties of polypropylene and the compounds that are produced during pyrolysis. © 2022 by the authors.